2017
DOI: 10.1101/185355
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pervasive epistasis modulates neurodevelopmental defects of the autism-associated 16p11.2 deletion

Abstract: Rare CNVs such as the 16p11.2 deletion are associated with extensive phenotypic heterogeneity, complicating disease gene discovery and functional evaluation. We used RNA interference in Drosophila melanogaster to evaluate the phenotype, function, and interactions of conserved 16p11.2 homologs in a tissue-specific manner. Using a series of quantitative methods for assessing developmental and neuronal phenotypes, we identified multiple homologs that were sensitive to dosage and showed defects in cell proliferati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 103 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…So far, we have considered the effect of each CNV gene independently, when, in reality, the genes may not be acting independently. A Drosophila model for 16p11.2 genes has shown evidence of epistasis between genes within a CNV as a modifier of phenotype 40 . If there are 16p11.2 traits in humans also driven by epistasis, our single-gene screen would not have detected the appropriate genes for those traits.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, we have considered the effect of each CNV gene independently, when, in reality, the genes may not be acting independently. A Drosophila model for 16p11.2 genes has shown evidence of epistasis between genes within a CNV as a modifier of phenotype 40 . If there are 16p11.2 traits in humans also driven by epistasis, our single-gene screen would not have detected the appropriate genes for those traits.…”
Section: Limitationsmentioning
confidence: 99%
“…However, this mutation neither caused ASD in all deletion carriers, nor was responsible for ASD in some non-carrier family members. Non-human models for the 16p11.2 and 22q11.2 CNVs, as well as knockouts for individual genes are available in mouse, zebrafish, and fruit flies [37][38][39][40][41][42] , but have not successfully mapped individual genes in these CNVs to brain-related traits [29][30][31] . Different zebrafish studies of 16p11.2 homologs have implicated different genes as phenotype drivers, as well as showed that most were involved in nervous system development 38,39,43 .…”
Section: Introductionmentioning
confidence: 99%